PELAKSANAAN PERAN PERAWAT SEBAGAI ADVOKAD DALAM PEMBERIAN INFORMED CONCENT TINDAKAN ECT PREMEDIKASI DI RSJD Dr. AMINO GONDHOUTOMO PROVINSI JAWA TENGAH - -, Kandar; Suryani, Maria; -, Tofi’ah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Background: ECT is a medical procedure performed on a patient with bipolar disorder and unipolar. Permenkes 290 / Menkes / PER / III / 2008, regarding 2, verse 1 describes "all medical action to be performed on the patient must to be agreement". Professional nurses, can play a role in giving informed consent as a client advocate. The purpose of this study is describe the role of nurses as an advocate in giving informed concent of action ECT (Electro convulsive Therapy) Premedication at RJD Dr. Amino Gondhohutomo Semarang. Methods: This research use method of qualitative research with phenomenological approach. This is a descriptive study with research data collection method using interviews at 6 nurses and triangulation at 3 families. Data collection tool using interview, video and mobile phones. Results: Researchers found four themes, each theme has one to two sub-themes. The first theme, describe the preparation of action ECT Premedikaksi . The second theme, explaining the role of the nurse as an advocate in giving informed concent. The third theme, explaining the difficulties of nurse in giving informed concent. The fourth theme, depicts the events nurse in the process of giving informed concent ECT Premedication.Conclusion: Nurses in the provision the role of advocacy in giving informed concent act as a witness, giving education, intermediaries doctor with family. Some nurse, doing assigment is not accordance with authority and responsibility.Keywords: role of the nurse, Informed concent, ECT Premedication